Analisis Perilaku Pengguna Fintech Berdasarkan Model UTAUT: Studi Kasus pada Mahasiswa Universitas XYZ - Pian TA , Suprianus (Universitas Boyolali, 2025)
Students as Generation Z or millennials are not only consumers but also agents of change in the adoption of financial technology. However, research exploring their behaviour based on the UTAUT framework is still limited, especially in the context of XYZ University. This study aims to analyse the factors that influence the behaviour of fintech usage by students at XYZ University using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, which is expanded with the variables of trust, perceived security, and financial literacy. The research method used was a quantitative approach with a survey technique involving 185 student respondents who had used fintech services, which were then analysed using Partial Least Square–Structural Equation Modelling (PLS-SEM). The results show that performance expectancy, effort expectancy, social influence, trust, perceived security, and financial literacy have a significant effect on behavioural intention, while facilitating conditions do not have a significant effect on intention but have a positive effect on actual use. In addition, behavioural intention is proven to be the main predictor of actual fintech use by students. These findings confirm that benefits, convenience, trust, security, and financial literacy are key factors driving fintech adoption, while infrastructure serves as a facilitator of actual use. This study has practical implications for campus administrators, fintech service providers, and regulators to increase adoption by providing real value, simple interfaces, applied financial literacy, and strengthening security and trust aspects.